The diagnostic value of three sacroiliac joint pain provocation tests for sacroiliitis identified by magnetic resonance imaging. (4th March 2017) - Arnbak, B; Jurik, AG; Jensen, RK; Schiøttz-Christensen, B; van der Wurff, P; Jensen, TS
Abstract : Objectives : The aim of the current study was to investigate the diagnostic value of three sacroiliac (SI) joint pain provocation tests for sacroiliitis identified by magnetic resonance imaging (MRI) and stratified by gender. Method : Patients without clinical signs of nerve root compression were selected from a cohort of patients with persistent low back pain referred to an outpatient spine clinic. Data from Gaenslen's test, the thigh thrust test, and the long dorsal sacroilia ligament test and sacroiliitis identified by MRI were analysed. Results : The median age of the 454 included patients was 33 (range 18–40) years and 241 (53%) were women. The prevalence of SI joints with sacroiliitis was 5%. In the whole study group, only the thigh trust test was associated with sacroiliitis, the area under the receiver operating characteristic (ROC) curve (AUC) was 0.58 [95% confidence interval (CI) 0.51–0.65], sensitivity 31% (95% CI 18–47), and specificity 85% (95% CI 82–87). In men, sacroiliitis was associated with all the SI joint tests assessed and multi-test regimens, with the greatest AUC found for at least one positive out of three tests [AUC 0.68 (95% CI 0.56–0.80), sensitivity 56% (95% CI 31–79), and specificity 81% (95% CI 77–85)]. In women, no significant associations were observed between the SI joint tests and sacroiliitis. Conclusions : Only in men were the SI joint tests found to be associated with sacroiliitis identified by MRI. Although, the diagnostic value was relatively low, the results indicate that the use of SI joint tests for sacroiliitis may be optimized by gender-separate analyses.